(untitled) (Biomedical Research and Therapy, 2018)
Introduction: Acute myocardial infarction (AMI) is a leading cause of mortality worldwide for which several risk factors have been identified. Kisspeptin is a multifunctional peptide observed in atherosclerotic plaques. This study aimed to compare kisspeptin serum levels in AMI patients and healthy individuals. Methods: This case-control study was conducted on patients visiting the Cardiology department of Peymanieh Hospital, Jahrom University of Medical Sciences, Iran. Participants were randomly divided into a case and a control groups; the former consisting of 90 AMI patients and the latter of 90 healthy individuals with no cardiac diseases. Blood samples were collected from the participants who also completed the given questionnaire. The enzyme-linked immunosorbent assay (ELISA) test was used to determine kisspeptin levels following serum separation from collected blood samples. Data analysis was performed in SPSS-19 using descriptive (mean and standard deviation) and analytical (The Mann-Whitney U test) statistical tests. Results: The mean age of treatment and control groups was 60.91 and 61.72 years, respectively. The majority (73.3%) of participants in this study were men. Kisspeptin serum concentrations were demonstrated to be significantly lower in the case group than the control group (P<0.001). The results of Mann-Whitney U test revealed that kisspeptin serum concentrations of case and control groups did not have a significant relationship with such variables as gender, smoking, and ST-segment elevation and non-ST-segment elevation (P>0.05). Conclusion: The results revealed that kisspeptin serum concentrations of AMI patients were significantly lower than those of healthy individuals. Accordingly, kisspeptin deficiency appears to be a risk factor for AMI. However, due to the multifunctional nature of this peptide, further studies are necessary to discover its precise mechanism of action.